2018
DOI: 10.1016/j.ccell.2018.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Actionable Activating Oncogenic ERBB2/HER2 Transmembrane and Juxtamembrane Domain Mutations

Abstract: Summary Deregulated HER2 is a target of many approved cancer drugs. We analyzed 111,176 patient tumors and identified recurrent HER2 transmembrane domain (TMD) and juxtamembrane domain (JMD) mutations, including G660D, R678Q, E693K and Q709L. Using a saturation mutagenesis screen and testing of patient-derived mutations we found several activating TMD and JMD mutations. Structural modeling and analysis showed that the TMD/JMD mutations function by improving the active dimer interface or stabilizing an activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(134 citation statements)
references
References 79 publications
8
112
0
Order By: Relevance
“…To assess the therapeutic implications of molecular events in our set of variants, we used Database of Evidence for Precision Oncology (DEPO; http://depo-dinglab.ddns.net) that focuses on specific mutations (STAR Methods) and casts therapeutic projections based on FDA-approved therapies, clinical trials, and published clinical evidence [28]. Of note, 2 variants in the PDGFRA gene (p.[Arg817Cys] in exon 18 and p.[Leu660Phe] in exon 14) found in MM were already described as a target of imatinib and an FDA-approved targeted therapy for GIST patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess the therapeutic implications of molecular events in our set of variants, we used Database of Evidence for Precision Oncology (DEPO; http://depo-dinglab.ddns.net) that focuses on specific mutations (STAR Methods) and casts therapeutic projections based on FDA-approved therapies, clinical trials, and published clinical evidence [28]. Of note, 2 variants in the PDGFRA gene (p.[Arg817Cys] in exon 18 and p.[Leu660Phe] in exon 14) found in MM were already described as a target of imatinib and an FDA-approved targeted therapy for GIST patients.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a TCGA cohort comprising 74 tumors revealed 13.5% of TP53 mutations [16]. Hmeljak et al [16] showed that TP53 is one of the MPM driver genes, together with BAP1, SETD2 , and NF2 , and is associated with aggressive behavior [16, 28]. They showed 13 TP53 mutations, mainly SNV type, missense type, and in exons 5–8 (all these alterations were found in 10/13 mutated cases), as found by us, but in different nucleotides [16].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations or deletions in EGFR and HER2 result in ligand-independent receptor activation, indicating that in addition to being activated in the presence of ligand, ERBBs are actively inhibited in the absence of ligand (25)(26)(27)(28)(29)(30). The mechanism for this autoinhibition remains incompletely understood, however.…”
Section: Introductionmentioning
confidence: 99%
“…ERBB2 (HER2) mutations have emerged as a novel biomarker and occur by the majority in patients without HER2 amplification [2], but also in HER2-amplified cases [53]. Evidence is mounting that recurrent ERBB2 mutations lead to increased activation of the HER2 receptor in tumors classified as HER2-normal [2,51,95]. Activating ERBB2 mutations have been shown to confer therapy resistance against standard of care drugs such as trastuzumab and lapatinib [53], but can be overcome using pan-HER tyrosine kinase inhibitors such as neratinib [2,96,97,53].…”
Section: Discussionmentioning
confidence: 99%